XAB2, a novel tetratricopeptide repeat protein involved in transcription-coupled DNA repair and transcription - Nakatsu, Y; Asahina, H; Citterio, E; Rademakers, S; Vermeulen, W; Kamiuchi, S; Yeo, J P; Khaw, M C; Saijo, M; Kodo, N; Matsuda, T; Hoeijmakers, J H; et al. (The Journal of biological chemistry, 2000)
Nucleotide excision repair is a highly versatile DNA repair system responsible for elimination of a wide variety of lesions from the genome. It is comprised of two subpathways: transcription-coupled repair that accomplishes efficient removal of damage blocking transcription and global genome repair. Recently, the basic mechanism of global genome repair has emerged from biochemical studies. However, little is known about transcription-coupled repair in eukaryotes. Here we report the identification of a novel protein designated XAB2 (XPA-binding protein 2) that was identified by virtue of its ability to interact with XPA, a factor central to both nucleotide excision repair subpathways. The XAB2 protein of 855 amino acids consists mainly of 15 tetratricopeptide repeats. In addition to interacting with XPA, immunoprecipitation experiments demonstrated that a fraction of XAB2 is able to interact with the transcription-coupled repair-specific proteins CSA and CSB as well as RNA polymerase II. Furthermore, antibodies against XAB2 inhibited both transcription-coupled repair and transcription in vivo but not global genome repair when microinjected into living fibroblasts. These results indicate that XAB2 is a novel component involved in transcription-coupled repair and transcription.